Analysis of The Level of Satisfaction of Outpatients tt Smart Medica Clinic with an Importance Performance Analysis Approach - Yosha Santoso Putra; Innocentius Bernarto (Enrichment : Journal of Management, 2022)
This study aims to find out how far the satisfaction level of outpatients at Smart Medica Clinic in the dimensions of Tangibility, Reliability, Responsiveness, Assurance and Empathy. This research is a descriptive study. The study was conducted at Smart Medica Clinic, Sekayu, Musi Banyuasin, South Sumatra, Indonesia, on 162 outpatients as a target population. The data collection technique is carried out by distributing questionnaires using accidental sampling. The data obtained were then analyzed using the Importance Performance Analysis (IPA) method with the help of the SPSS for Windows application program ver. 27. The results of this study show that outpatients of Smart Medica Clinic are not satisfied with outpatient services in the dimensions of Tangibility, Reliability, Responsiveness, Assurance and Empathy.